PEMANFAATAN SISTEM INFORMASI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN TERHADAP MUTU LAYANAN ADMINISTRASI - Akbar, Abu Rizal; Siraj, Arifuddin; Yaumi, Muhammad (Prodi PAI STIT Sunan Giri Bima, 2023)
This research article aims to analyze and find the significance of the influence of the use of management information systems (MIS) in decision making on the quality of administrative services at the Graduate School of UIN Alauddin Makassar. This research is a field research with ex post facto method through a quantitative approach. Respondents in this study were 62 graduate students taken at random as many as 10% of 618 college students. The data collection technique used was a questionnaire then analyzed descriptively and inferentially using simple linear regression analysis. The results of this study indicate that: the reality of the use of MIS in decision making at the Graduate School UIN Alauddin Makassar is 65.8% of the expected criteria, indicating that there are still 34.2% that need to be improved; the reality of the quality of administrative services at the Graduate School of UIN Alauddin Makassar 64.6% of the expected criteria, indicating that there are still 35.4% that need to be improved; the use of MIS in decision making has a positive effect of 30.7% on the quality of administrative services and has a significant effect on the Graduate School of UIN Alauddin Makassar.